An Areal analysis of family planning program performance in rural Bangladesh - Osteria, T. (Working paper / International Centre for Diarrhoeal Disease Research, Bangladesh ;, 1979)
Survey covers selected villages of Matlab Thana, Comilla District, Bangladesh.